Использование инновационных форм и методов в процессе обучения - Пархаева, Е.А. (My University, 2016)
In this article, the author describes the forms and methods of the organization of work of pupils at physics and technology lessons. In the course of formation of the physical and technical knowledge and skills of students the teacher applies the next technologies: the new content in education, problem – based learning, project, research, information and communicative technologies, critical thinking
Keywords: teacher; pupil; innovation; technology; problem; decision; reflection